STUDI KUALITAS ORGANOLEPTIK DAGING BABI GULING DARI BABI BALI DAN BABI LANDRACE - I G. N. P., Widiadnyana; Sriyani, N. L. P.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2017)
This study aims to find out the organoleptic comparison of landrace grilled pig meats. Bali pig use in the study was came from Gerokgak Village Buleleng District, the pig was fed traditionally and landrace pig on another hand came from Dalung and was fed with commercial feeding. The weight of both pigs were similar. The pork that will be tested was part of Longissimus dorsi and the organoleptic variables observed were colour, texsture, flavour and overall acceptance was used complete randomized design with a comparison of two different meat samples, the data obtained were analyzed using Non-parametric analysis. The result of the organoleptic test showed the meat colour of landrace pig 10.14% not significantly different than bali pig. While panelist preferences on aroma, texture, flavour, and overall acceptance on bali pig treatment were differs markedly 11.69%, 13.88%, 14.70%, and 15.78% respectively compared to landrace pig treatment. Based on the result of the study can be concluded that of the overall organoleptic test conducted overall acceptance of panelists prefer bali pig compared to landrace pig.